Catholic education at the coalface of a kaleidoscope of identities. (2nd January 2022) - Stapleton, Catherine
ABSTRACT: Globalisation, migration, socio-political shifts, and access to the internet are increasing the religious and belief diversity of Irish society. This flux presents challenges for young people who are endeavouring to establish a secure identity. The focus of this research was to understand how the identity development of post-primary students of minority faith or worldview, is impacted by attending a school with a Catholic ethos. The research methodology was qualitative. To provide an opportunity for students to voice their experiences, 18 post-primary students of minority faith or worldview were interviewed. Thematic analysis was used to identify the findings. Reflecting on an interpretivist paradigm, the epistemology which underpinned this research was constructivism. While theories of adolescent moral and identity development alongside theories of othering, conformity, and agency supported the research study. The findings report some students struggled to find a secure identity due to conflicting societal, school, peer, and family beliefs. Perceived negative stereotyping of their beliefs created feelings of otherness with implications for students' self-esteem. Students' sense of belonging and well-being was impacted on by Catholic-centric school practices combined with current provision to 'opt-out' from Religious Education classes. However, the research also found human agency resulted in a kaleidoscope of student responses to the inherent challenges of adolescent identity development.